Delgada línea: entre el clientelismo y la confianza institucional. Estudio en dos distritos de Lima Metropolitana - Cohaila Ramos, Edwin (2016)
This article attempts to observe the existence of certain similarities between trust that can be established between individuals and their local political institution, with habitual ways of relating that adjoin political clientelism. Certain similarities that point to question whether clientelism can be accommodated as a way to build relationships, create links and bring the individual to the political institution. The local political institution will be studied, and observe how relations have been builtin two districts of the same geographical area, through qualitative and quantitative tools. It will be noted that the usual way of relating learned still present and mobilizes the ways of acting individuals; therefore links with clientelistic characteristics are plausible to generate trust relationships.